Predicting Work-Family and Familywork Conflict from Work and Family Domain: A Longitudinal Study - Zaiton Hassan; Hana Hamidi (International Journal of Management Studies, 2012)
Although work-family conflict studies are available in Malaysia, most rely on cross-sectional design and focus on women. This study uses the longitudinal design on a heterogeneous sample which is aimed to enhance the understanding of the antecedents of work-family conflict (WFC) and familywork conflict (FWC) from work and family demands and resources. The respondents were 296 employees in diverse industries from six public and private organizations in Kuching, Sarawak. Two surveys were conducted over a three-month interval. Structural Equation Modeling via AMOS 7.0 was used to analyse the data. The study found that the respondents reported higher WFC than FWC. Demands from work predicted WFC positively while resources from work predicted WFC negatively. None of the demands and resources from work and family predicted FWC. The findings implied the importance of organizations in influencing the work-family balance of the employees.